Comparative study of young shoots and the mature red headed cabbage as antioxidant food resources with antiproliferative effect on prostate cancer cells. Issue 70 (26th November 2020) - Drozdowska, Mariola; Leszczyńska, Teresa; Koronowicz, Aneta; Piasna-Słupecka, Ewelina; Dziadek, Kinga
Abstract : Young shoots of red cabbage could be a good source of phytochemicals with potential anticancer activity. Abstract : The increasing knowledge on health benefit properties of plant origin food ingredients supports recommendations for the use of edible plants in the prevention of diet related diseases, including cancer. The beneficial effects of young shoots of red cabbage can be attributed to their mixture of phytochemicals possessing antioxidant and potential anticancer activity. The objective of this study was to compare the content of bioactive compounds, including HPLC analysis of polyphenols and antioxidant activity of young shoots of red cabbage and the vegetable at full maturity. The content of vitamin C and polyphenols in juices obtained from young shoots and the mature vegetable were also determined. The other aim of this study was to confirm the hypothesis that juice of young shoots more effectively, compared to juice of the mature vegetable, reduces the proliferation of prostate cancer cell lines DU145 and LNCaP in vitro . A significantly higher content of vitamin C and carotenoids, as well as a higher antioxidant activity were found in edible young shoots in comparison to the mature vegetable. In addition, studies have shown higher amount of vitamin C in the juice of young shoots than in the juice of the mature vegetable and similar content of polyphenolic compounds. The level of total polyphenol content in the studied plant samples did not differ significantly. Flavonoids were the main polyphenols in young shoots and juice obtained from them, while phenolic acids were dominant in the mature vegetable and in juice obtained from it. The juice of young shoots has shown stronger in vitro anti-proliferation effect against prostate cancer cells than juice of the mature vegetable.